State Obligations toward Unauthorized Parking Attendants in the Fulfilment of the Right to Work and Urban Public-Space Governance - Rama Putra Alvareza (Punggawa Law Review, 2026)
This article examines state obligations toward unauthorized parking attendants in Indonesia by placing the issue at the intersection of informal labor protection, the constitutional right to work, and urban public-space governance. Unauthorized parking attendants are commonly treated as public-order offenders because they collect parking fees without official authorization, operate outside registered parking systems, and often contribute to congestion, tariff uncertainty, illegal levies, and leakage of local revenue. This view is legally relevant but incomplete. It becomes analytically weak when state policy relies only on raids, removal, administrative sanctions, or criminalization without addressing the socio-economic structure that produces unauthorized parking work. Using normative legal research with statutory, conceptual, and literature-based approaches, this article argues that unauthorized parking attendants must be understood as informal workers located in a transitional legal position. Their practices may be unlawful, but their social position reflects limited access to decent work, weak social protection, and gaps in urban governance. The state must therefore distinguish between illegal parking practices that require control and the persons behind those practices who remain rights-bearing citizens. The article proposes a model of state obligation based on three layers: respecting the dignity of informal workers, protecting the public and attendants from illegal levies and exploitation, and fulfilling access to lawful work through data collection, selective registration, social security, training, digitalized payment systems, and job transition schemes.